2020
DOI: 10.1111/gcb.15004
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and empirical validation of long‐term carbon sequestration in forests (France, 1850–2015)

Abstract: The development of appropriate tools to quantify long‐term carbon (C) budgets following forest transitions, that is, shifts from deforestation to afforestation, and to identify their drivers are key issues for forging sustainable land‐based climate‐change mitigation strategies. Here, we develop a new modeling approach, CRAFT (CaRbon Accumulation in ForesTs) based on widely available input data to study the C dynamics in French forests at the regional scale from 1850 to 2015. The model is composed of two interc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 91 publications
1
29
0
Order By: Relevance
“…More recently, Le Noë et al. (2020) showed that during the last 50 years the carbon stock of forests in France has grown from increases in biomass density. They also discussed how trees serve as a pathway for carbon from the atmosphere into soils.…”
Section: Forest Transition Of Area and Density: Case Nationsmentioning
confidence: 99%
See 3 more Smart Citations
“…More recently, Le Noë et al. (2020) showed that during the last 50 years the carbon stock of forests in France has grown from increases in biomass density. They also discussed how trees serve as a pathway for carbon from the atmosphere into soils.…”
Section: Forest Transition Of Area and Density: Case Nationsmentioning
confidence: 99%
“…We propose that Forest Transitions played a growing role, not yet fully appreciated in accelerating the carbon sink in terrestrial ecosystems. Across the large areas of global lands where Forest Transition has occurred (Meyfroidt & Lambin, 2011), vegetation biomass carbon builds up responding to an expansion of both forest area and forest density (Le Noë et al., 2020).…”
Section: Carbon Sink and Forest Transitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, natural ageing of these broadleaved production systems might counterbalance GS expansion resulting from active coniferous afforestation programs. A full understanding of causal forest management processes of this expansion requires mandatory explorations of diameter-structured budgets of GS and growth/harvest flux balance across ownership categories, making more global analyses insufficient (Le Noë et al 2020). Such analyses at hand with NFI data are underway.…”
Section: Forest Changes Across Ownership and Composition Stratamentioning
confidence: 99%